KUALITAS TIDUR PADA REMAJA DI SMP NEGERI 1 TAHUNA - Montolalu, Laetitia I.; Ponidjan, Tati S.; Sumilat, Vervando J. (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2024)
Introduction: Good quality sleep is very important for a person's health and well-being, especially for teenagers. But unfortunately, many teenagers experience sleep quality problems which can affect their health and well-being. Adolescent sleep quality problems can also affect academic performance, behavior, and overall physical and mental health. Objective: To determine the quality of sleep of teenagers at SMP Negeri 1 Tahuna. Method: Quantitative Research uses an observational design with descriptive research type. The population in this study was 105 teenagers at SMP Negeri 1 Tahuna starting from grades 7-9. The sampling technique used purposive sampling with the sample criteria being teenagers aged 13-15 years or middle teenagers, willing to be respondents and not having medical conditions that affect sleep, so that a sample of 52 respondents was obtained. Results: The majority of respondents were 14 years old with a total of 38 people (73.07%), while the majority of gender characteristics were female, namely 33 people (63.46%). In general, 38 teenagers had poor sleep quality (73.08%), while 14 teenagers had good sleep quality (26.92%). Conclusion: Students generally have poor sleep quality. After knowing the picture of adolescent sleep quality, this study recommends that future researchers provide actions such as complementary therapy or other interventions to improve the quality of adolescent sleep so that they can improve academic performance, behavior and overall physical and mental health